Pembuatan Jamu Tradisional untuk Menjaga Daya Tahan Tubuh - Liana Liana (Nuras : Jurnal Pengabdian Kepada Masyarakat, 2025)
Health and endurance are important aspects in maintaining quality of life, especially amidst increasing public awareness of the importance of a healthy lifestyle. One natural way that has been used for generations in Indonesia is by consuming traditional herbal medicine. This activity was carried out in RT. 06, Punia Jamaq Environment, Punia Village, Mataram City, with the aim of introducing and increasing public understanding of the benefits and how to make traditional herbal medicine as an alternative to maintain endurance. The activity methods include counseling, direct demonstrations of making herbal medicine, and practice by participants using natural ingredients such as ginger, turmeric, temulawak, and lemongrass. The results of this activity showed high enthusiasm from participants and increased knowledge about the benefits and how to make herbal medicine. This activity is expected to encourage people to utilize traditional medicine as part of efforts to maintain health independently and sustainably.